A VIKOR-based approach for assessing the service performance of electric vehicle sharing programs: A case study in Beijing. (1st April 2017) - Xu, Fangqiu; Liu, Jicheng; Lin, Shuaishuai; Yuan, Jiahang
Abstract: Electric vehicle sharing (EVS) has been recognized as a promising solution to growing issues of traffic congestion, air pollution and insufficient parking spaces. This study assesses service performance of EVS programs in order to help operators improve service quality and attract more customers. First, this paper identifies 22 criteria from the perspectives of electric vehicles, charging stations, payment and Internet services and establishes the evaluation index system. Then a VIsekriterijumska Optimizacija I Kompromisno Resenje (VIKOR) based approach is proposed with three main steps including processing the criteria values represented by crisp values, interval numbers and linguistic variables, determining integrated criteria weights and assessing alternatives by VIKOR method. Next, a case study is provided to verify the feasibility and effectiveness of the proposed method. Three candidate EVS programs in Beijing are evaluated and ranked according to their scores. A sensitivity analysis and a comparative analysis of different methods are also performed to show that the proposed method is capable to assess service performance of EVS programs. Finally, suggestions are made for program operators according to assessment result.